Dynamic fiscal competition: a political economy theory - Calin Arcalean (Center for Economic Studies and ifo Institute (CESifo), 2019)
I develop a political economy theory of dynamic fiscal competition via public spending and debt. With internationally mobile capital, strategic policies generate two cross-border externalities that voters in each country fail to internalize: (1) an increase in public spending that bolsters capital accumulation but also (2) a race to the top in public debt which crowds out capital. The relative size of these two externalities varies with the number of financially integrated countries and interacts with the domestic political conflict between young and old voters. Despite residence based taxation, capital tax rates are lower under strategic policies than under coordination. Furthermore, they may decline with financial integration. Strategic policies lead to lower long run output and welfare relative to coordination but are preferred by subse-quent generations of voters if the number of financially integrated countries is low or the political weight of the young is high.
Keywords: H20; H40; H60; 330; political economy; public spending; public debt; economic integration